2018
DOI: 10.3389/fendo.2018.00500
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Vitamin D Status During Pregnancy on Mother and her Developing Child

Abstract: Pregnancy is a time of tremendous growth and physiological changes for mother and her developing fetus with lifelong implications for the child. The concert of actions that must occur so mother does not reject the foreign tissue of the fetus is substantial. There must be exquisite balance between maternal tolerance to these foreign proteins of paternal origin but also immune surveillance and function such that the mother is not immunocompromised. When this process goes awry, the mother may experience such preg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 113 publications
(178 reference statements)
1
75
0
2
Order By: Relevance
“…41,42 Altogether, we speculate that the BN rat could be a useful model to investigate the relationships between vitamin D deficiency during pregnancy, the increase in maternal pro-inflammatory cytokines, and the development of pregnancy disorders such as hypertension, proteinuria, and placental insufficiency. The changes of key proteins identified in the DIGE/MS and IPA analysis were studied in age-matched female rats starting at non-pregnancy (NP) and throughout pregnancy days 9, 13, 17, and 21 (n = 4/rat strain per gestational age; total 20/rat strain).…”
Section: Ically-determined Immune Phenotypes With Non-pregnant Bn Ratsmentioning
confidence: 94%
See 1 more Smart Citation
“…41,42 Altogether, we speculate that the BN rat could be a useful model to investigate the relationships between vitamin D deficiency during pregnancy, the increase in maternal pro-inflammatory cytokines, and the development of pregnancy disorders such as hypertension, proteinuria, and placental insufficiency. The changes of key proteins identified in the DIGE/MS and IPA analysis were studied in age-matched female rats starting at non-pregnancy (NP) and throughout pregnancy days 9, 13, 17, and 21 (n = 4/rat strain per gestational age; total 20/rat strain).…”
Section: Ically-determined Immune Phenotypes With Non-pregnant Bn Ratsmentioning
confidence: 94%
“…7 BN dams show a drastic fivefold drop in the levels of bioactive vitamin D, and supplementation with calcitriol significantly improved fetal/placental weights and fetal viability as shown by litter sizes at birth. 7 This is of great interest, as maternal vitamin D deficiency has also been associated with pre-eclampsia and fetal-origins of postnatal asthma 41,42. Altogether, we speculate that the BN rat could be a useful model to investigate the relationships between vitamin D deficiency during pregnancy, the increase in maternal pro-inflammatory cytokines, and the development of pregnancy disorders such as hypertension, proteinuria, and placental insufficiency.…”
mentioning
confidence: 95%
“…Whether vitamin D intake during pregnancy has an impact on the development of childhood asthma is unclear as one metaanalysis found no significant association between prenatal vitamin D status and risk of asthma. However, recently, it was suggested that lower maternal vitamin D intake during pregnancy is associated with increased risk of children wheezing and being diagnosed with asthma in the first 10 years [96], indicating a role for vitamin D in the development of childhood asthma.…”
Section: Vitamin D In Asthma Exacerbationmentioning
confidence: 99%
“…The maternal calcitriol deficiency during lung development in animal models modifies the expression of genes involved in organ development, branching morphogenesis, and regulation of inflammation process [91]. Therefore, several respiratory parameters may be affected, including the reduction in lung volume, vital capacity and oxygen saturation, and increases in airway smooth muscle mass and airway contractility [92][93][94]. All of these changes alter normal lung physiology and might compromise the survival of the litters.…”
Section: Cholecalciferolmentioning
confidence: 99%